Tờ trình đề nghị xây dựng Luật Dầu khí (thay thế Luật Dầu khí 1993, sửa đổi bổ sung năm 2000 và 2008) (Số: 9601/TTr-BCT) - Bộ Công thương (2020)
Toàn văn Tờ trình đề nghị xây dựng Luật Dầu khí (thay thế Luật Dầu khí 1993, sửa đổi bổ sung năm 2000 và 2008) (Số: 9601/TTr-BCT)